Prenatal ultrasound and MRI findings of temporal and occipital lobe dysplasia in a twin with achondroplasia. (September 2014) - Pugash, D.; Lehman, A. M.; Langlois, S.
ABSTRACT Thanatophoric dysplasia, hypochondroplasia and achondroplasia are all caused by FGFR3 (fibroblast growth factor receptor 3) mutations. Neuropathological findings of temporal lobe dysplasia are found in thanatophoric dysplasia, and temporal and occipital lobe abnormalities have been described recently in brain imaging studies of children with hypochondroplasia. We describe twins discordant for achondroplasia, in one of whom the prenatal diagnosis was based on ultrasound and fetal MRI documentation of temporal and occipital lobe abnormalities characteristic of hypochondroplasia, in addition to the finding of short long bones. Despite the intracranial findings suggestive of hypochondroplasia, achondroplasia was confirmed following postnatal clinical and genetic testing. These intracranial abnormalities have not been previously described in a fetus with achondroplasia. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd